Lean Management to support Choosing Wisely in healthcare: the first evidence from a systematic literature review. - CREMA, MARIA; VERBANO, CHIARA (International Journal for Quality in Health Care, 2017)
Purpose: Choosing Wisely (CW) is an emergent approach to identify and reduce unnecessary care, such as tests and treatments that do not add value for patients and may even cause harm. The purpose of this paper is to investigate whether and how Lean Healthcare Management (LHM) can support CW objectives, focusing on customer needs and on waste elimination.Data Sources: A systematic literature review has been performed in Scopus, PubMed and Web of Science.Study Selection: Peer reviewed articles published in English language have been selected. Papers were considered if they regarded LHM and its possible support for achieving CW objectives. Data extraction. The links between the LHM purposes of adoption and the pursued CW objectives were investigated. Moreover, LHM tools, practices and interventions to support CW were grasped.Results Of Data Synthesis: Sixteen articles were included in the analysis. Links between the identified LHM purposes of adoption and CW objectives were discovered: through process understanding, optimization, evaluation and control, LHM contributes to the reduction of overuses in healthcare, but also to the delivery of a more effective and evidence-based care (EBC). Moreover, it provides an objective approach useful for choosing the most cost-effective solution among different alternatives.Conclusions: Results highlight how LHM, and with which tools and practices, can be adopted to enhance the healthcare appropriateness pursued by CW, paving the way for interesting future research about this emerging topic.